Menu Costs and the Neutrality of Money - Caplin, Andrew S.; Spulber, Daniel F. (Quarterly Journal of Economics, 1987)
A model of endogenous price adjustment under money growth is presented. Firms follow (s,S) pricing policies, and price revisions are imperfectly synchronized. In the aggregate, price stickiness disappears, and money is neutral. The connection between firm price adjustment and relative price variability in the presence of monetary growth is also investigated. The results contrast with those obtained in models with exogenous fixed timing of price adjustment.